2011
DOI: 10.2118/145158-pa
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Controlled Gravity Drainage in Fractured Porous Media

Abstract: Oil production from a fractured reservoir with a gas cap and an oil zone usually takes place at a constant withdrawal rate until gas breakthrough; thereafter, the pumping rate is influenced by the presence of gas. Knowing the effect of pumping rate on production performance before gas breakthrough and selecting optimum pumping rates are necessary. In this paper, the concept of "critical production rate" (CPR) is introduced; it is the production rate at which a porous medium has a recovery factor (RF) equal to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…[52] However, for this case, the wettability was considered to be constant during the tests. [16,19] Given the matrix threshold pressure and by using the J-function, fracture threshold pressure was set to 100 Pa. A matrix pore size distribution index was chosen as 2, based on usual values in the literature for glass beads; this parameter for the fracture was set to 4 for proper modelling of the fluid front behaviour and capillary force in the fracture. [53] …”
Section: Parameters Of Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…[52] However, for this case, the wettability was considered to be constant during the tests. [16,19] Given the matrix threshold pressure and by using the J-function, fracture threshold pressure was set to 100 Pa. A matrix pore size distribution index was chosen as 2, based on usual values in the literature for glass beads; this parameter for the fracture was set to 4 for proper modelling of the fluid front behaviour and capillary force in the fracture. [53] …”
Section: Parameters Of Modellingmentioning
confidence: 99%
“…[13][14][15] Several experimental studies for different types of gravity drainage processes were conducted in unconsolidated models. [16][17][18][19] However, accurate determination of the parameters requires mathematical modelling of this process. There are some mathematical models in the literature, [5,10,15,20] though most previously proposed models have many simplifying assumptions, because of the complexities associated with the gravity drainage process and non-linearity of the governing equations.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the rate of finger growth was largely independent of the type of heterogeneity and that the level of bypassed oil decreased linearly with increasing dimensionless distance travelled by the front. Zendehboudi et al [6] performed an experimental study of controlled gravity drainage in fractured porous media and studied the sensitivity to several system parameters. They found that the critical production rate and recovery factor could be correlated to the fracture/matrix permeability ratio and Bond number.…”
Section: Introductionmentioning
confidence: 99%
“…They attributed this difference to variations in the experimental features such as the permeability heterogeneity at the matrix-fracture boundary (Firoozabadi and Tan 1994). Zendehboudi and Chatzis (2011) have recently conducted an experimental work to understand and investigate the interactions between capillary and gravity forces of controlled gravity drainage in NFRs. They used unconsolidated glass bead packs surrounded by two vertical fractures on the sides.…”
Section: Introductionmentioning
confidence: 99%